Prevalence of Contraceptive Used by Married Couples in Chattogram Hill Tracts - Zafreen, Farzana; Rahman, Md Mustafizur; Razzak, Md Abdur; Rahman, Md Habibur; Wahab, Md Abdul (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Bangladesh is a densely populated country with high fertility rate. Contraception is an essential method for reducing fertility rate. Use of contraceptive depends on couples’ socio-cultural, education and economic condition. Chattogram hill tract is the least economically developed area where, education and health care facilities are hard to reach. Objectives: To find out the prevalence of contraceptive used bymarried couples of selected rural community of Khagrachari District. Materials and Methods: This descriptive cross sectional study was conducted from January to December 2017on 300married women age ranging from 15 to 45 years reported to outpatient department of Border Guard Hospital,Guimara,Khagrachari were selectedpurposively after informed written consent.All the necessary data were collected in a pretested structured questionnaire by face to face interview. Results: Among the 300 respondents highest 42.7% was in age group of 15-25 years, 60% were married for more than 10 years, 38.3% were illiterate, 89.7% were housewives and 55.7% had monthly family income between five to ten thousands taka. Respondents’ ethnicity was Bengali 51.7%, Marma 18.3%, Tripura 18.7% and Chakma 34(11. 3%). About 53% respondents were using contraceptives among them95.6% were using temporary methods;60.4% oral contraceptive pill followed by injectable 15.8% and condom 9.4%. Barrier to contraceptives use was fear of side effects 21.9% followed by husbands’ non co-operation 24.9% and religious bar 22.7%. Conclusion: Prevalence of contraceptive use in Chattogram Hill Tract is lower than the overall rate of the country. Appropriate measure should be taken to increase the contraceptive use rate so that total fertility can be controlled. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 120-122